Callio lab: an underground and above ground,laboratory—overview and prospects for high energy and applied physics - Joutsenvaara, Jari; Puputti, Julia; Holma, Marko; Kotavaara, Ossi (Frontiers in Physics, 2024)
This overview provides a comprehensive insight into Callio Lab, a versatile multidisciplinary research platform, by describing the events and actions that have led to the development of the project-based, pay-by-service approach to organizing and economically running the research activities, a mandatory approach for a platform operating without governmental funding. The research platform has a maximum depth of 1.4 kilometers underground, equivalent to approximately 4100 meters of water equivalent (m.w.e.). The flat-overburden mine configuration of Callio Lab minimizes cosmic-ray background interference, making it an ideal setting for low-background experiments, particularly in neutrino and dark matter research. The main-level galleries, with dimensions up to 12 meters wide, 30-40 meters long, and 8 meters tall, provide ample space for research activities, with the potential for even more extensive galleries based on Laguna design studies. Callio Lab has a history with several small and medium-scale cosmic ray and low-background experiments. This overview highlights the site's inherent characteristics, revealing promising opportunities for high-energy and applied physics research and applications across various scientific domains.